Hanging on Cliff: Workforce Development and Sustainability in the Face of Working Age Population Decrease in South Korea - JIN LEE (Adult Education Research Conference, 2017)
To evaluate and design effective policy to mitigate, and ultimately overcome the crisis of demographic cliff, the systemic structure of labor force decrease of Korea was modeled with system dynamics method.
Keywords: demographic cliff; workforce development; South Korea